Neurotrophin-4 promotes the specification of trophectoderm lineage after parthenogenetic activation and enhances porcine early embryonic development - Kim, Mirae; Lee, Joohyeong; Cai, Lian; Choi, Hyerin; Oh, Dongjin; Jawad, Ali; Hyun, Sang-Hwan (Frontiers in Cell and Developmental Biology, 2023)
Neurotrophin-4 (NT-4), a neurotrophic factor, appears to affect early embryonic development because it is secreted not only by neurons but also by oviductal and uterine epithelial cells. However, no studies have characterized the effects of NT-4 on early embryonic development in pigs. In this study, we applied the experimental model of parthenogenic embryos (PA). Herein, we investigated the effect of NT-4 supplementation during the in vitro culture (IVC) of embryos, analyzed the transcription levels of specific genes, and outlined the first cell lineage speciﬁcation for porcine PA-derived blastocysts. We confirmed that NT-4 and its receptor proteins were localized in both the inner cell mass (ICM) and trophectoderm (TE) in porcine blastocysts. Across different concentrations (0, 1, 10, and 100 ng/mL) of NT-4 supplementation, the optimal concentration of NT-4 to improve the developmental competence of porcine parthenotes was 10 ng/mL. NT-4 supplementation during porcine IVC significantly (p < 0.05) increased the proportion of TE cells by inducing the transcription of TE lineage markers (CDX2, PPAG3, and GATA3 transcripts). NT-4 also reduced blastocyst apoptosis by regulating the transcription of apoptosis-related genes (BAX and BCL2L1 transcripts) and improved blastocyst quality via the interaction of neurotrophin-, Hippo-yes-associated protein (Hippo-YAP)- and mitogen-activated protein kinase/extracellular regulated kinase (MAPK/ERK) pathway. Additionally, NT-4 supplementation during IVC significantly (p < 0.05) increased YAP1 transcript levels and significantly (p < 0.01) decreased LATS2 transcript levels, respectively, in the porcine PA-derived blastocysts. We also confirmed through fluorescence intensity that the YAP1 protein was significantly (p < 0.001) increased in the NT-4-treated blastocysts compared with that in the control. NT-4 also promoted differentiation into the TE lineage rather than into the ICM lineage during porcine early embryonic development. In conclusion, 10 ng/mL NT-4 supplementation enhanced blastocyst quality by regulating the apoptosis- and TE lineage specification-related genes and interacting with neurotrophin-, Hippo-YAP-, and MAPK/ERK signaling pathway during porcine in vitro embryo development.